Menthol tobacco use is correlated with mental health symptoms in a national sample of young adults: implications for future health risks and policy recommendations. Issue 1 (December 2016) - Cohn, Amy; Johnson, Amanda; Hair, Elizabeth; Rath, Jessica; Villanti, Andrea
Abstract Background Depression and anxiety are correlated with greater nicotine dependence, smoking persistence, and relapse back to smoking after a quit attempt. Menthol cigarette smoking, which is prevalent in young adults, is associated with nicotine dependence, progression to regular smoking, and worse cessation outcomes than non-menthol smoking. Few have established a link between menthol tobacco use, beyond just smoking, with mental health in this high-risk age group. This study examined the association of menthol tobacco use to anxiety and depression in a national sample of young adults. Methods Data were from Waves 1 through 7 (n = 9720, weighted) of the Truth Initiative Young Adult Cohort, a national sample of men and women aged 18 to 34 assessed every 6-months. Demographics, past 30-day use of non-menthol and menthol tobacco products, and current alcohol, marijuana, and other drug use were assessed among those with depression and anxiety. Results Thirty nine percent of current tobacco users used menthol as their preferred brand. Using a cross-sectional analysis (collapsed across waves), past 30-day menthol tobacco was uniquely associated with greater odds of both depression and anxiety, beyond the effects of demographic and substance correlates and non-menthol tobacco product use. Conclusions Menthol is disproportionately used among young adults tobacco users with mental health problems, above and beyond the impact of a variety of other mental health and tobacco use risk factors. Findings suggest a strong link between menthol tobacco use and poor health outcomes. Policies should be developed to deter menthol tobacco use in vulnerable groups.